2017
DOI: 10.1371/journal.pone.0174839
|View full text |Cite
|
Sign up to set email alerts
|

MiR-9-3p augments apoptosis induced by H2O2 through down regulation of Herpud1 in glioma

Abstract: MicroRNAs are short, single-stranded non-coding RNA molecules that function as regulators of tumor progression in various cancers, including glioma. The present study sought to investigate the biological functions of miR-9-3p in glioma progression. The results of a microRNA microarray indicated that microRNA-9-3p (miR-9-3p, miR-9*) is down-regulated in high-grade (grades III and IV) gliomas compared with non-tumor tissues. These results were confirmed with real-time PCR. The miR-9-3p expression level was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Glioma, a kind of malignancy arising from glial cells in the brain, is the most common malignant tumours occurring in the central nervous system and accounting for 78% of intracranial primary tumours 1, 2. Glioma usually exhibits a series of malignant features, including extensive, rapid and aggressive progression, resistance to surgery, radiotherapy and chemotherapy, all of which lead to the poor prognosis for most patients 3.…”
Section: Introductionmentioning
confidence: 99%
“…Glioma, a kind of malignancy arising from glial cells in the brain, is the most common malignant tumours occurring in the central nervous system and accounting for 78% of intracranial primary tumours 1, 2. Glioma usually exhibits a series of malignant features, including extensive, rapid and aggressive progression, resistance to surgery, radiotherapy and chemotherapy, all of which lead to the poor prognosis for most patients 3.…”
Section: Introductionmentioning
confidence: 99%
“…miR-9-3p has been demonstrated to regulate biological functions in multiple types of cancer. For example, Yang et al (33) reported that H 2 O 2 -induced apoptosis of glioma cells was facilitated by miR-9-3p through downregulation of Herpud1 expression. In another study, miR-9-3p inhibited cell proliferation by targeting the PDZ-binding motif TAZ in hepatocellular carcinoma (34).…”
Section: Discussionmentioning
confidence: 99%
“…Low expression of miR-9-3p leads to a high level of Herpud 1, which prevents glioma cell apoptosis [ 61 ]. The function of Herpud1 is not totally figured out, but there is more and more evidence that it plays an important role in ER-membrane-associated protein degradation (ERAD) by transferring ubiquitin protein from endoplasmic reticulum (ER) to proteasome degradation [ 62 ].…”
Section: Discussionmentioning
confidence: 99%